Relationship between Job engagement, security, training and employees workplace behaviour in selected industries in Ogun and Lagos states, Nigeria (2014)
A motivated employee cares about his/her workplace and work to contribute towards the organizational success, longevity and profitability. There are motivational factors, intrinsic or extrinsic, which influences employees' workplace behaviour (performance and level of satisfaction). This study examined the relationship between Job Engagement, Security, Training and Employees Workplace Behaviour in Selected Industries in Ogun and Lagos states, Nigeria. The descriptive research design was used for the study. The population comprised of employees in service and manufacturing industries in Ogun and Lagos States. A questionnaire tagged "Job Engagement, Security, Training on Employees Workplace Behaviour Questionnaire" was the main instrument used for the research. From the service industries, a random sampling technique was used to select civil service, the teaching service and manufacturing firms from both states. A total of 235 respondents were used as sample for the study. A Cronbach Alpha reliability obtained for each of the sections in the questionnaire is: Engagement at work (0.74); job security (0.67); training at work (0.80) and workplace behaviour (0.87).Three hypotheses were tested at 0.05 level of significance. Finding showed that there was significant relationship between job engagement and workplace behaviour of employees (r = .502, n= 235, P < .05), that there was significant relationship between job security and workplace behaviour of employees(r = .504, n= 235, P < .05). Furthermore, the study revealed that there was significant relationship between job training and work-place behaviour of employees (r = .648, n= 235, P < .05). The study therefore recommends that employers should assure their employees of their job security, given opportunities for job engagement. Also, employees should be trained to improve their skills and knowledge so as to make employees care about their workplace and create positive workplace behaviour.